2004
DOI: 10.21273/hortsci.39.3.574
|View full text |Cite
|
Sign up to set email alerts
|

Compositional and Sensory Analyses of Sweetpotatoes after X-ray Irradiation Quarantine Treatment

Abstract: Sweetpotato [Ipomoea batatas (L.) Lam.] roots of two Hawaii-grown clones were treated with 100 to 600 Gy X-ray irradiation and evaluated for quality before and after cooking. Root moisture content, surface color, and glucose and fructose concentrations were not affected by irradiation treatment for either the red-skin, yellow-flesh (RY) or the white-skin, purple-flesh (WP) clones. Firmness decreased at higher doses for RY roots, but not for WP roots. The alcohol insoluble sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Grated root tissue (10 g) between 100 and 500 Gy (Lu et al,1986). In a previous study, a 600 Gy dose did not reduce the overall quality or taste of purple-fl eshed and yellow-fl eshed sweetpotatoes (Wall, 2004). Hallman (2001) also found that orange-fl eshed roots treated with a 300 Gy dose did not differ from control roots in color or organoleptic ratings.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Grated root tissue (10 g) between 100 and 500 Gy (Lu et al,1986). In a previous study, a 600 Gy dose did not reduce the overall quality or taste of purple-fl eshed and yellow-fl eshed sweetpotatoes (Wall, 2004). Hallman (2001) also found that orange-fl eshed roots treated with a 300 Gy dose did not differ from control roots in color or organoleptic ratings.…”
mentioning
confidence: 90%
“…Hallman (2001) also found that orange-fl eshed roots treated with a 300 Gy dose did not differ from control roots in color or organoleptic ratings. However, slight decreases in fi rmness and starch concentrations were observed in some roots 2 weeks after treatment with doses below 600 Gy (Wall, 2004). Specifi cally, fi rmness decreased linearly with increasing irradiation dose for yellow-fl eshed roots, but not for purple-fl eshed roots (Wall, 2004).…”
mentioning
confidence: 98%
“…In sweet potatoes, variety and irradiation dose are important factors that affect the firmness during storage. Wall () reported that firmness of red‐skin yellow‐fleshed sweet potatoes decreased linearly with increasing irradiation dose up to 600 Gy, but white‐skin purple‐fleshed sweet potatoes retained firmness. Consequently, irradiation at 1000 Gy did not increase softening of PFSP cubes compared with nonirradiated samples on any storage day (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Wall () indicated that irradiation at 400‐Gy dose increased redness in the internal colour of PFSP roots compared with control samples. Consistent with this result, a duller colour was observed in 1000 Gy treated samples after 14 days (Table ), but based on hue angle value ( h °), no colour difference was determined in any samples on day 14.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation